2015
DOI: 10.1007/s11695-015-1724-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bone Metabolism in Morbidly Obese Patients After Bariatric Surgery: A Meta-Analysis

Abstract: BMD was significantly decreased, while bone turnover was elevated, and bone remodeling was accelerated following bariatric surgery. Basal bone metabolism should be evaluated preoperatively. To prevent secondary hyperparathyroidism and bone loss, calcium and vitamin D should be monitored closely and supplemented accordingly after the surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
105
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(118 citation statements)
references
References 47 publications
6
105
0
7
Order By: Relevance
“…Increases in bone turnover markers have also been observed in response to gastric banding and sleeve gastrectomy [10]. A meta-analysis of 10 studies involving a total of 344 patients confirmed that whilst total body, femoral neck, lumbar spine and pelvic BMD were significantly decreased post-surgery, serum or urinary concentrations of NTX were significantly elevated [54]. This meta-analysis noted interesting differences in serum concentrations of nutrients that are important for the maintenance of bone mass, namely calcium and vitamin D. That is, serum calcium concentrations were significantly reduced post-bariatric surgery, although no difference could be found in serum concentrations of vitamin D [54].…”
Section: Effect Of Bariatric Surgery On Bonementioning
confidence: 94%
See 1 more Smart Citation
“…Increases in bone turnover markers have also been observed in response to gastric banding and sleeve gastrectomy [10]. A meta-analysis of 10 studies involving a total of 344 patients confirmed that whilst total body, femoral neck, lumbar spine and pelvic BMD were significantly decreased post-surgery, serum or urinary concentrations of NTX were significantly elevated [54]. This meta-analysis noted interesting differences in serum concentrations of nutrients that are important for the maintenance of bone mass, namely calcium and vitamin D. That is, serum calcium concentrations were significantly reduced post-bariatric surgery, although no difference could be found in serum concentrations of vitamin D [54].…”
Section: Effect Of Bariatric Surgery On Bonementioning
confidence: 94%
“…BMD has been found to be significantly decreased post bariatric surgery, with differing results between surgery types [10,[54][55][56]. Most available information about the effects of bariatric surgery on bone comes from studies on RYGB.…”
Section: Effect Of Bariatric Surgery On Bonementioning
confidence: 99%
“…It belongs to the «safe organ preserving surgery», has a high effi ciency rate and is commonly chosen for treating extreme cases of obesity. However, issues with changes in bone metabolism have recently been brought to light in association to bariatric surgery [6][7][8][9].…”
Section: а о никоненко є і гайдаржі м бужґаmentioning
confidence: 99%
“…In addition, they reported signifi cant increase in serum or urinary N-telopeptide and in bone -specifi c alkaline phosphatase, accompanied by a decrease in bone mineral density (BMD) [8].…”
Section: а о никоненко є і гайдаржі м бужґаmentioning
confidence: 99%
See 1 more Smart Citation